THE INFLUENCE OF ACCOUNTING STUDENTS' UNDERSTANDING OF GOVERNMENT ACCOUNTING STANDARDS ON INTEREST IN WORKING AS PUBLIC SECTOR ACCOUNTANTS - Mia Fidela; Iman Waskito (ZILLZELL MEDIA PRIMA, 2024)
This study aims to analyze the effect of accounting students' understanding of Government Accounting Standards (SAP) on their interest in working as public sector accountants. The type of research used is associative with a quantitative approach, which examines the causal relationship between the independent variable (students' understanding of SAP) and the dependent variable (interest in working as public sector accountants). The study was conducted at the University of Mataram, with a population of all students majoring in accounting in semesters five, seven, and nine. Sampling used a purposive sampling technique, where the sample was students who had passed the Public Sector Accounting I and II courses and were still active. Primary data were collected through questionnaires distributed to respondents, and this research instrument has been tested for validity and reliability. The results of the analysis show that students' understanding of SAP has a significant effect on interest in working as public sector accountants. The regression model used meets the classical assumptions, so the results of this study are considered valid and reliable. These findings indicate that a good understanding of SAP can encourage students' interest in pursuing a career in the public sector, as well as provide a strong basis for further research in the fields of government accounting and public sector workforce.